2020
DOI: 10.1016/j.celrep.2020.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Correlates of Tolerance and Lethality in Mice Predict Ebola Virus Disease Patient Outcomes

Abstract: Highlights d Host responses produce distinct Ebola virus outcomes in genetically diverse mice d Tolerant outcomes result from early inflammatory responses and sustained regulation d Lethality is linked to early gene suppression and uncontrolled inflammation d Murine transcriptional profiles can be used to predict clinical outcome in humans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…Mice transplanted with human immune cells or human immune system (HIS) mice, have been widely used to study human-specific viral infections 24,25 and the combination of HIS and ACE2 expression could help to further explore the efficacy of vaccines and therapies, in particular those that modulate human immune cells. Similarly, previous studies using the CC model of genetic diversity, a panel of recombinant inbred mice with expanded susceptibility to viruses that normally do not cause disease in laboratory mice can be used to enhance virus disease susceptibility, however, infection remains heavily dependent on a functional entry receptor 26,27 . CC mice were previously used with mouse-adapted SARS-CoV to identify mechanisms of pathogenesis and genetic loci that determine susceptibility 28 .…”
Section: Other Mouse Models and Approachesmentioning
confidence: 99%
“…Mice transplanted with human immune cells or human immune system (HIS) mice, have been widely used to study human-specific viral infections 24,25 and the combination of HIS and ACE2 expression could help to further explore the efficacy of vaccines and therapies, in particular those that modulate human immune cells. Similarly, previous studies using the CC model of genetic diversity, a panel of recombinant inbred mice with expanded susceptibility to viruses that normally do not cause disease in laboratory mice can be used to enhance virus disease susceptibility, however, infection remains heavily dependent on a functional entry receptor 26,27 . CC mice were previously used with mouse-adapted SARS-CoV to identify mechanisms of pathogenesis and genetic loci that determine susceptibility 28 .…”
Section: Other Mouse Models and Approachesmentioning
confidence: 99%
“…Both host effects [ 5 , 6 , 31 ] and the presence of other infections [ 9 ] will undoubtedly contribute to the outcome in EVD. The host response to EBOV infection is a major determinant of disease severity in EVD [ 5 ], as well as the timing and magnitude of transcriptional regulatory networks, where early induction of inflammatory gene expression is associated with an asymptomatic course of the disease [ 32 ]. The host response at the acute stage in many of the patients covered in this study was investigated previously [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of COVID-19 patients found that early administration of IFN-α2b treatment following hospital admission drastically improved outcomes, while late administration increased mortality rates compared to untreated patients [17]. Furthermore, studies investigating the prognosis in Ebola virus (EBOV) infection found that a potent and early type I IFN signature and its subsequent immune activation is indicative of greater survival outcomes in humans [18][19][20]. Viruses can also inhibit elements of the IFN signaling pathway in order to promote their replication and survival.…”
Section: The Paradoxical Role Of Type I Ifns In Inflammation and Disease Tolerancementioning
confidence: 99%